Analysis of the Application of #Sambo Hashtags to Computer-Mediated Communication on Instagram - Irwansyah, Nabil Putra; Sufa, Siska Armawati; Sari, Ratna Puspita; Brumadyadisty, Garry; Yenny, Yenny (PT. Riset Press International, 2024)
This study delves into analyzing the utilization of the hashtag #SAMBO in computer-mediated communication on Instagram. In contemporary digital communication, hashtags are pivotal tools, shaping online discourse and facilitating content discovery. Focusing on the hashtag #SAMBO, this research investigates its prevalence, purpose, and impact within Instagram's Computer-Mediated Communication (CMC). Through a meticulous content analysis approach, this study explores the patterns, trends, and underlying themes associated with using #SAMBO across various Instagram posts. The research meticulously examines the contextual nuances in which #SAMBO is employed, shedding light on its diverse roles in shaping conversations, user engagement, and community building. Furthermore, this study explores the hashtag's relevance in specific social, cultural, or political contexts, unveiling its potential to influence public opinion and societal attitudes. By scrutinizing the content and user interactions associated with #SAMBO, this research provides valuable insights into the dynamics of contemporary digital communication. The findings of this study offer a comprehensive understanding of the hashtag's multifaceted functions within Instagram's CMC framework. This research contributes to the broader discourse on social media communication by unraveling the complexities of hashtag usage and bridging the gap between digital rhetoric and user behavior. Ultimately, this analysis enhances our comprehension of the evolving digital language, shedding light on how hashtags shape online narratives, foster community identity, and influence public discourse on social media platforms.